EVALUATION IN THE GENRE OF FILM REVIEW - E. Yu. Garanina (Вестник Кемеровского государственного университета, 2013)
The article deals with the development history of the genre of film review, its peculiarities and the ways of expressing evaluation – the category forming film review genre and text. The reaction register being the dominant communicative register of film review is revealed. The article contains some examples of the expressing evaluation on different linguistic levels.